Synthesis, characterization, and thermal investigation of some metal complexes containing polydentate ONO-donor heterocyclic Schiff base ligand - Sönmez, M; Levent, A; Sekerci, M (Maik Nauka/Interperiodica, 2004)
Cu(II), Co(II), Ni(H), and Zn(II) metal complexes with new heterocyclic Schiff base derived from 1-amino-5-benzoyl-4-phenyl-IH-pyrimidine-2-one and 3-methoxysalicylaidehyde have been synthesized and characterized on the basis of elemental analyses, electronic IR, and H-1 NMR spectra, and also by aid of molar conductivity measurements, maenetic moment measurements, and thermogravinietric analyses. It has been found that the Schiff base behaves as a neutral bidentate (NO) and tridentate (ONO) ligand forming chelates with 1 : 2 (metal : ligand) stoichiometry. Octahedral configuration is suggested for metal complexes. The conductivity data for the Ni(II) complexes are consistent with those expected for a 1 : 2 electrolyte.
Keywords: Coordination-Compounds; Copper(Ii); Co(Ii)